Proces i stracenie Ludwika XVI w świetle prasy warszawskiej z lat 1792-1793 - Karkocha, Małgorzata (Acta Universitatis Lodziensis. Folia Historica, 2010)
The purpose of the article is to present the fates of Louis XVI after the revolution on 10 August 1792. The king, devoid of the executive power, was imprisoned with family in Temple, where he was supposed to wait for the further decision about his affair. National Convention which gathered on 20 September 1792 was about to decide on his fate. The question we discuss on the basis of the polish information press, which was appearing in Warsaw in the years 1792-1793. In that time two periodicals were published: ‘Gazeta Warszawska’ and ‘Korespondent Warszawski’. During the first weeks after 10 August nothing showed that Louis would be executed. Only small group of the radical club activists demanded his death. The configuration of political forces in the Convention was profitable for Louis. The Girondins had majority and they wanted to save the king at any price. First of all they lingered over bringing a suit as long as possible and when it occurred to be unavoidable, they were trying to exchange the death penalty for the life imprisonment. The opposite party, the Montagnards, demanded to put Louis into jail immediately, to sentence him to death and execute the verdict to give the others an example. Finding Louis' letters in the secret hiding place in Tuileries on 20 November, giving evidence that he was conspiring with counterrevolutionaries and Austrians, with whom France waged a war, made the further postponement of the trial impossible. The next day the Assembly called into existence the Commission of 12 Members, which was supposed to take care of the inventory of founded correspondence. On 6 December, a new Commission consisted of 21 members was established. The Commission presented in the Convention on 10 December the act of Louis’ accusation. The Assembly interrogated ex-king two times, on 10 and 26 December. On 14 January 1793, the Convention passed free questions for the deputies: Is Louis guilty of treason? Should the Convention's sentence be sanctioned by people? What should be the punishment for Louis? The voting on two first questions took place on 15 January. Louis was found guilty almost unanimously with 693 votes. A few deputies abstained from voting. A motion about appellation to the people failed in the proportion of 424 to 283. On 17 January, the Convent passed a death penalty for Louis. The execution took place on 21 January. The death of French monarch brought grief to all Europe and quickened the formation of the First Coalition.